The Columnar-lined Mucosa in the Distal Esophagus. A Preliminary Study in Baboons - RUBIO, CARLOS A. (2009)
BACKGROUND: For anatomists, the cardia is a portion of the stomach. However, at the histological level, the cardiac mucosa, described as columnar-lined with mucus-producing glands (CLMMG), is for some pathologists part of the stomach (already present at birth) and for others a metaplastic change of the esophagus induced by gastro-esophageal reflux (GER). MATERIALS AND METHODS: The distal esophagus and the proximal stomach of 5 adult male baboons were removed en bloc at autopsy. The distance between the most distal part of the squamous epithelium of the esophagus and the first oxyntic fundic gastric gland (representing the entire CLMMG) was assessed using an ocular microscale. RESULTS: The length of the CLMMG varied from 1.2 mm to 12.4 mm. The CLMMG had replaced the squamous epithelium of the distal esophagus in all 5 baboons. DISCUSSION: Regurgitation with rumination is a natural physiological, daily, recurrent process in baboons that leads to GER. The luminal cytoplasmic vacuoles with neutral mucins contained in the columnar cells and the neutral mucins produced by the mucin glands buffer the low pH of the gastric juices that reflux into the distal esophagus. This protective action against the acid refluxate cannot be achieved by the squamous epithelium. CONCLUSION: The results of this preliminary investigation suggest that in baboons, CLMMG is an adaptation process of the esophageal mucosal to the low pH microenvironment conveyed by protracted GER.